2016
DOI: 10.1007/s12593-015-0190-6
|View full text |Cite
|
Sign up to set email alerts
|

A New “Trapdoor technique” for Fixation of Displaced Greater Tuberosity Fractures of the Shoulder

Abstract: Isolated greater tuberosity fractures of the proximal humerus are frequently displaced posteriorly and superiorly by the pull of the rotator cuff. This displacement can lead to a decline in function if left untreated. Traditionally these fractures have been treated surgically using screw fixation. On occasions this metalwork can remain prominent and potentially cause impingement. We present a new surgical Btrapdoort echnique for fixation of isolated greater tuberosity fractures which can avoid these problems a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Generally, superior migration of the GT may result in subacromial impingement and weakness in abduction, whereas posterior migration may result in a loss of external rotation. 15 Bono et al, 2 in their biomechanical study, showed that the glenohumeral abduction force of the deltoid was significantly increased by 16% and 27% by superior displacements of the GT of 0.5 cm and 1 cm, respectively. Therefore, the current literature recommends operative treatment of GT fractures with >5 mm of displacement.…”
Section: Discussionmentioning
confidence: 98%
“…Generally, superior migration of the GT may result in subacromial impingement and weakness in abduction, whereas posterior migration may result in a loss of external rotation. 15 Bono et al, 2 in their biomechanical study, showed that the glenohumeral abduction force of the deltoid was significantly increased by 16% and 27% by superior displacements of the GT of 0.5 cm and 1 cm, respectively. Therefore, the current literature recommends operative treatment of GT fractures with >5 mm of displacement.…”
Section: Discussionmentioning
confidence: 98%
“…If conservative treatment fails, it is of utmost importance to correct the valgus of the humeral neck and then reduce the GT fracture by surgery. Internal fixation can be performed using screws, a proximal humerus locking plate, or a proximal humerus locking intramedullary nail [27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…20) Using the same suture-tensioning method, we performed a concomitant 3.5-mm LCP hook plate fixation for isolated GT fractures and an augmentation tension suture fixation of the rotator cuff, using cortical screws and two differently sized washers. For severely comminuted fractures, we applied the trapdoor technique using suture anchor developed by McLaughlin-Symon et al 11) by replacing the sutureless anchor with a 3.5-mm LCP hook plate.…”
Section: Discussionmentioning
confidence: 99%
“…4) Various fixation methods for GT fractures exist, including the transosseous suture fixation, the cannulated screw fixation, the plate fixation, the cerclage wire fixation, and the arthroscopic suture anchor fixation. 3,[5][6][7][8][9][10][11] For patients with olecranon fractures or those who have undergone olecranon osteotomies, 3.5-mm locking compression plate (LCP) hook plate (Synthes, West Chester, PA, USA) is commonly used for fixation. For GT fixation, this plate has lower profile than the proximal humeral plates and, therefore, lower the chances of postoperative subacromial impingements.…”
Section: Introductionmentioning
confidence: 99%